2014
DOI: 10.1016/j.mod.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A developmental genetic analysis of the lysine demethylase KDM2 mutations in Drosophila melanogaster

Abstract: Post-translational modification of histones plays essential roles in the transcriptional regulation of genes in eukaryotes. Methylation on basic residues of histones is regulated by histone methyltransferases and histone demethylases, and misregulation of these enzymes has been linked to a range of diseases such as cancer. Histone lysine demethylase 2 (KDM2) family proteins have been shown to either promote or suppress tumorigenesis in different human malignancies. However, the roles and regulation of KDM2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
44
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 63 publications
8
44
2
Order By: Relevance
“…Because both PRC1 and PRC2 can directly interact with DNA and the histone modifications catalyzed by the other complex, each complex could putatively recruit the other or synergize to promote higher recruitment at overlapping sites. Flies have homologues of Pcl and Kdm2 proteins but fly Pcl lacks sequence specificity in vitro (Choi et al, 2017) and fly Kdm2 is dispensable for viability (Shalaby et al, 2017;Zheng et al, 2014). Furthermore, while PRC1-catalyzed H2AK119ub enriches PcG proteins in mouse and fly embryonic cell cultures, Cooper et al, 2014;Fursova et al, 2019;Kahn et al, 2016), it has a minimal effect on PRC2 localization and Polycomb silencing in many fly tissues (Gutiérrez et al, 2012;Pengelly et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because both PRC1 and PRC2 can directly interact with DNA and the histone modifications catalyzed by the other complex, each complex could putatively recruit the other or synergize to promote higher recruitment at overlapping sites. Flies have homologues of Pcl and Kdm2 proteins but fly Pcl lacks sequence specificity in vitro (Choi et al, 2017) and fly Kdm2 is dispensable for viability (Shalaby et al, 2017;Zheng et al, 2014). Furthermore, while PRC1-catalyzed H2AK119ub enriches PcG proteins in mouse and fly embryonic cell cultures, Cooper et al, 2014;Fursova et al, 2019;Kahn et al, 2016), it has a minimal effect on PRC2 localization and Polycomb silencing in many fly tissues (Gutiérrez et al, 2012;Pengelly et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…dRAF was reported to produce the bulk of Drosophila H2AK118ub and mutations in the Kdm2 gene were said to enhance the homeotic phenotypes of heterozygous Pc mutants (15). However, a recent study suggests that Kdm2 is not essential for fly viability (17) questioning the importance of dRAF for PcG repression. Finally, Drosophila RING1 can potentially form a dimer with a third Drosophila PCGF protein called L(3)73Ah.…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila has 13 KDMs, with only one conserved KDM2 ortholog, dKdm2 (LAGAROU et al 2008;KAVI and BIRCHLER 2009;ZHENG et al 2014;HOLOWATYJ et al 2015). Based on analyses of 13 mutant alleles of dKdm2 gene, we have concluded that dKdm2 is not required for normal development in Drosophila (ZHENG et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Drosophila has 13 KDMs, with only one conserved KDM2 ortholog, dKdm2 (LAGAROU et al 2008;KAVI and BIRCHLER 2009;ZHENG et al 2014;HOLOWATYJ et al 2015). Based on analyses of 13 mutant alleles of dKdm2 gene, we have concluded that dKdm2 is not required for normal development in Drosophila (ZHENG et al 2014). This notion is unexpected for the following reasons: first, dKdm2 has been identified as a subunit of the dRING-associated factor (dRAF) complex, a Polycomb group (PcG) complex that was proposed to play critical roles in coordinating trans-histone regulation by replacing the active H3K36me2 marker with a repressive mono-ubiquitinated H2A K118 (H2AK118ub or H2Aub) marker (LAGAROU et al 2008).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation